A generic methodology for processing route synthesis and design based on superstructure optimization. (2nd November 2017) - Bertran, Maria-Ona; Frauzem, Rebecca; Sanchez-Arcilla, Ana-Sofia; Zhang, Lei; Woodley, John M.; Gani, Rafiqul
Highlights: A generic methodology for sustainable process synthesis-design using superstructure optimization. Databases with a common data structure are described for the systematic storage and retrieval of data. Super-O: a user interface for synthesis of processing routes. An ethanol biorefinery case study. A carbon dioxide capture and utilization case study. Abstract: In this paper, a systematic framework for novel and sustainable synthesis-design of processing routes is presented along with the associated computer-aided methods and tools. In Stage 1, superstructure optimization is used to determine the optimal processing route(s). In Stage 2, the design issues are resolved and targets for improvement are identified through the use of integrated tools. In Stage 3, new alternatives are generated using the selected route and the previously identified targets. In addition to the various computer-aided tools, two special tools are presented: (1) a database employing a specially developed knowledge representation system, and (2) Super-O, a software interface that guides users through the formulation and solution of synthesis problems. Super-O transfers data between the different tools, including a library of generic models, representing a wide range of processing options. Application of the synthesis and design stages is highlighted through two case studies (biorefinery and carbon capture-utilization).